2021
DOI: 10.3390/insects12020169
|View full text |Cite
|
Sign up to set email alerts
|

Models Applied to Grapevine Pests: A Review

Abstract: This paper reviews the existing predictive models concerning insects and mites harmful to grapevine. A brief conceptual description is given on the definition of a model and about different types of models: deterministic vs. stochastics, continuous vs. discrete, analytical vs. computer-based, and descriptive vs. data-driven. The main biological aspects of grapevine pests covered by different types of models are phenology, population growth and dynamics, species distribution, and invasion risk. A particular emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 86 publications
0
7
0
1
Order By: Relevance
“…However, here weather data collected from the time of sowing until the time of the aphids' first appearance were integrated to develop informative weather indices. This approach may also take care of various biological phenomenons of the pests (like life cycle) as well as of the crops (Lessio and Alma, 2021) . Kumar et al: Forewarning system for wheat aphids (2019) also found temperature and humidity as key contributing exogenous factors in their prediction models to determine the abundance of Trialeurodes vaporariorum in greenhouses.…”
Section: Web-enabled Systemmentioning
confidence: 99%
“…However, here weather data collected from the time of sowing until the time of the aphids' first appearance were integrated to develop informative weather indices. This approach may also take care of various biological phenomenons of the pests (like life cycle) as well as of the crops (Lessio and Alma, 2021) . Kumar et al: Forewarning system for wheat aphids (2019) also found temperature and humidity as key contributing exogenous factors in their prediction models to determine the abundance of Trialeurodes vaporariorum in greenhouses.…”
Section: Web-enabled Systemmentioning
confidence: 99%
“…Así pues, se encuentran en la literatura modelos, como el presentado por Touzeau en el año 1981 (Touzeau, 1981), y que se ha constituido como uno de los modelos más utilizados para representar el proceso de crecimiento de Lobesia botrana con relación a la temperatura. Trabajos más recientes, como los presentados por Lessio y Alma en (Lessio and Alma, 2021), presentaron un panorama amplio con relación al modelado de L. botrana y otras plagas que afectan el desarrollo de la vid, destacando que, si bien los modelos de caja negra o derivados del ajuste de datos, son utilizados para predecir el comportamiento o aparición de la polilla para ciertas condiciones climáticas dadas, carecen de una base conceptual que facilite su uso por parte de viticultores, enólogos, profesionales de soporte técnico, servicios fitosanitarios y otras partes interesadas. Para dar solución a lo anterior, se encuentran en la literatura, modelos semi físicos basados en primeros principios (FPBSM -por sus siglas en inglés) como el presentado en (Aguirre-Zapata et al, 2022).…”
Section: Introductionunclassified
“…This is due to at least two reasons: i) in agriculture measuring is economically expensive, and for many crops probably it will likely never be realistic to perform a continuous monitoring of all plants; ii) in order to plan effective treatments is important not only to measure the current status of the farm, but also to predict the future evolution of the infestations. Accordingly, in parallel with the technological research, it is fundamental to develop mathematical models able to describe and predict the evolution of the infestations [8].…”
Section: Introductionmentioning
confidence: 99%
“…Many scientists around the world are currently working on the mathematical modelling of insect pests population dynamics [8,9,10,11]. Pest population models are particularly important when pest management is performed through the release of natural enemies, the use of which is rapidly growing among farmers and is one of the core aspects of the so-called Integrated Pest Management (IPM) framework.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation